Analisis Penulisan Berita Pada Media Online Kompas.Com Dengan Struktur Piramida Terbalik Sebagai Pemanfaatan Media Ajar Melalui Tiktok di SMA - Fahera, Helsa; Musa, Safuri; Nuraini, Cut (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research is motivated by the development of the David Ozora persecution case which was published on the online media page Kompas.com. This can be seen based on the history of news publications in the February-March 2023 edition, there were 15 news reports that raised the persecution case. Based on the news findings, it can be analyzed regarding the 5W+1H elements and the inverted pyramid news structure. This study uses qualitative methods with documentation techniques for each news content. The results found based on observations of the 5W+1H elements and the inverted pyramid news structure found that the most dominant elements are what and who elements, while the news structure section has incomplete legs. Apart from that, the results of the analysis were also used for news text learning materials for class XII high school students in the form of audio-visual learning media in the form of videos through the TikTok application.